Novas configurações textuais do slogan publicitário na contemporaneidade - Reino, Luciana da Silva Souza (2019)
This research aimed to investigate new ways of both think and reconfigure the slogan in contemporary times. Based on the premise that today's slogans present new textual configurations, we chose Grounded Theory (GT) as the methodology that guided the construction of an empirical corpus and data codification. The corpus is composed of 1250 slogans taken from advertisements published in Veja magazine between 2001 and 2015, in addition to the construction and consequent analysis of categories that demonstrated the existence of regular textual structures, frequently used words and most common patterns in the composition of the slogans. To carry out the analysis and for the subsequent literature comparison proposed by the GT, we selected the studies in textual and stylistic syntax (CUNHA; CINTRA, 2017; HENRIQUES, 2011), language and discourse (BAKHTIN, 1997; KOCH, 2016).